INTERFAITH MARRIAGE IN INDONESIA: LOOKING FOR A LOOPHOLE - Tridiatno, Yoachim Agus (Universitas Sanata Dharma, 2023)
This research studies the life experience of interfaith marriage between Christian and Muslem. It aims to answer the following questions: (1) Do religious differences in interfaith marriage partners affect the success of building a family? (2) What are the factors that determine the success of building a family in interfaith couples? This research is qualitative study. The data were collected through the depth interview which were directly done face to face, and indirect interview through WhatsApp and Google Form. Forum Group Discussion was done also with some students who live in the interfaith marriage family. The respondents are cathegorized into the followings: (1) those living in the interfaith marriage between Christian and Muslem, (2) those who converted to other religions following that of the partners, (3) those who converted to the religion of the partners but then reconverted to their previous religions, (4) the parents of the children who do interfaith marriage, and (5) the children who live in the family with interfaith marriage. The results indicate that the difference of religion in the family is not the significant factor which determines the harmonious life in the family. Otherwise, tolerance, mutual concern, and the responsible attitude of each family member in their respective duties and roles are the most important factors. Therefore, the civil and religious laws which prohibit the interfaith marriage are actually not relevant. The civil law does not have authority to interfere the private sectors of family life. Then, religious law which prohibits the interfaith marriage must be revied and understood in its context to strive for the salvation of the religious people.